Serum Sulfonylurea Receptor-1 Levels After Acute Supratentorial Intracerebral Hemorrhage: Implication for Prognosis - Zhuge CJ; Zhan CP; Wang KW; Yan XJ; Yu GF (Neuropsychiatric Disease and Treatment, 2022)
Cheng-Jun Zhuge,1 Cheng-Peng Zhan,2 Ke-Wei Wang,1 Xin-Jiang Yan,2 Guo-Feng Yu2 1The Second School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 2Department of Neurosurgery, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, People’s Republic of ChinaCorrespondence: Guo-Feng Yu, Tel +86 570 3055179, Email quzhouguofengyu@163.comObjective: Sulfonylurea receptor-1 (SUR1) is implicated in acute brain injury. This study was designed to determine relationship between serum SUR1 levels and severity, early neurologic deterioration (END) plus clinical outcome after intracerebral hemorrhage (ICH).Methods: Serum SUR1 levels of 131 ICH patients and 131 healthy controls were quantified in this prospective, observational study. END was defined as an increase of 4 or more points in the National Institutes of Health Stroke Scale (NIHSS) score or death within 24 hours after admission. Patients with a modified Rankin scale (mRS) score of 3– 6 at 90 days following onset were considered to experience a poor outcome.Results: Serum SUR1 levels were substantially higher in patients than in controls. Serum SUR1 levels of patients were highly correlated with NIHSS score, Glasgow Coma Scale score, hematoma volume and ICH score. Compared with patients with END or mRS score of 0– 2, other remainders had significantly elevated serum SUR1 levels. Serum SUR1 levels independently predicted END and 90-day poor outcome. Under receiver operating characteristic curve, serum SUR1 levels significantly predicted END and a poor outcome at 90 days after hemorrhagic stroke and its predictive value was similar to those of NIHSS score, Glasgow coma scale score, hematoma volume and ICH score.Conclusion: Serum SUR1 levels are highly correlated with severity, END and poor outcome after hemorrhagic stroke, indicating that serum SUR1 may be useful for risk stratification and prognostic prediction of ICH.Keywords: Sulfonylurea receptor-1, intracerebral hemorrhage, early neurologic deterioration, functional outcome, severity